A Polynomial-based Pairwise Key Pre-distribution and Node Authentication Protocol for Wireless Sensor Networks - Fatemeh Banaie; Seyed Amin Hosseini Seno; Ismat Aldmour; Rahmat Budiarto (Universitas Ahmad Dahlan, 2015)
Continuous advances in the areas of sensor networks have made wireless sensor networks (WSNs) attractive for wide variety of applications, with vastly varying requirements and characteristics. As data sensed by nodes usually contains sensitive information, adherence to data protection requirements is vital in WSNs. This paper introduces a new robust key pre-distribution key management scheme using random polynomial functions and a matrix. The proposed mechanism significantly increases storage efficiency and enhances network resilience against node capture. The effectiveness of the mechanism is demonstrated by security analysis and a comparison to existing schemes.